2006
DOI: 10.1291/hypres.29.143
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Antihypertensive Prescription and Associated Blood Pressure Control in Japan

Abstract: The importance of tight blood pressure (BP) control has been established. We performed cross-sectional studies on the current status of BP control and the prescription and efficacy of antihypertensive drugs in hypertensive patients in Japan. The data were also evaluated in subgroups with or without diabetes mellitus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
98
4
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 29 publications
8
98
4
1
Order By: Relevance
“…Although the percentage of patients using diuretics in the present study was higher than that found in previous reports from Japan (3)(4)(5), the prescription rate of diuretics (8.6%) among patients with a history of stroke still seems to be low. In the Perindopril Protection against Recurrent Stroke study (PROGRESS), it was shown that combination therapy with an ACE-inhibitor (perindopril) and a diuretic (indapamide) appeared to reduce the risk of stroke (8).…”
Section: Number Of Diuretic Prescriptions (N)contrasting
confidence: 92%
See 3 more Smart Citations
“…Although the percentage of patients using diuretics in the present study was higher than that found in previous reports from Japan (3)(4)(5), the prescription rate of diuretics (8.6%) among patients with a history of stroke still seems to be low. In the Perindopril Protection against Recurrent Stroke study (PROGRESS), it was shown that combination therapy with an ACE-inhibitor (perindopril) and a diuretic (indapamide) appeared to reduce the risk of stroke (8).…”
Section: Number Of Diuretic Prescriptions (N)contrasting
confidence: 92%
“…The percentage of patients using diuretics (9.3%) in the J-HOME study was higher than that (4.0-5.4%) found in previous studies (3)(4)(5), but was similar to that found (12.6%) in another recent study (6). This trend could be attributable to the impact of recently published, large-scale intervention trials, such as the ALLHAT study, which emphasized the clinical significance of diuretics (1,16,17).…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…In Japan, CCBs have long been the most widely used antihypertensives, mainly because of their reliable blood pressurelowering effects (13). ARBs are a relatively new class of drugs that suppress the renin-angiotensin system in a manner similar to ACE inhibitors.…”
Section: Introductionmentioning
confidence: 99%